# What is the solution to the equation 3x + 2(x - 9) = 8x + x - 14?

**Solution:**

The given equation is 3x + 2(x - 9) = 8x + x - 14

On rearranging the equation,

3x + 2x - 18 = 8x + x - 14

Grouping of common terms,

5x - 18 = 9x - 14

9x - 5x = -18 + 14

4x = -4

x = -1

Therefore, the solution to the given equation is x = -1.

Example: **What is the solution to the equation 2x + 3(x - 8) = x - 16?**

**Solution:**

The given equation is 2x + 3(x - 8) = x - 16

On rearranging the equation,

2x + 3x - 24 = x - 16

Grouping of common terms,

5x - 24 = x - 16

5x - x = 24 - 16

4x = 8

x = 2

Therefore, the solution to the given equation is x = 2.

## What is the solution to the equation 3x + 2(x - 9) = 8x + x - 14?

**Summary:**

The solution to the equation 3x + 2(x - 9) = 8x + x - 14 is x = -1.

Math worksheets and

visual curriculum

visual curriculum